Unleashing the power of data with trusted AI a guide for board members and executives - Turner-Williams, Wendy (Packt Publishing Ltd., 2024)
Written by a distinguished leader and innovator who has been instrumental in spearheading digital, cloud, and AI transformations across global brands, Unleashing the Power of Data with Trusted AI is an indispensable resource that will make you AI-ready. This comprehensive guide is designed to meet the urgent need for clarity and to give you actionable insights into today's rapidly evolving landscape of AI and its fundamental driver - data. You'll delve into the exciting world of AI and its integration with data, uncover its significance, ethical considerations, and strategic applications with real-life success stories from industry giants like Starbucks, Netflix, and Siemens. You'll also witness first-hand how the integration of data and AI has reshaped markets and elevated customer experiences, and discover the future of generative AI based on several surveys and case studies. You'll gain an understanding of how AI has evolved across industries, empowering decision-making and fostering innovation. Tailored for board members, executives, innovators, and tech enthusiasts, this immersive guide will reshape your understanding of data and AI synergy. By the end of this guide, you'll be able to lead your teams, customers, partners, and organizations confidently and responsibly in the era of AI.
Includes bibliographical references
Keywords: Electronic data processing -- Management; Artificial intelligence; Intelligence artificielle; artificial intelligence